2020
DOI: 10.1096/fj.202001163r
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress in the dorsal root ganglia regulates large‐conductance potassium channels and contributes to pain in a model of multiple sclerosis

Abstract: Neuropathic pain is a common symptom of multiple sclerosis (MS) and current treatment options are ineffective. In this study, we investigated whether endoplasmic reticulum (ER) stress in dorsal root ganglia (DRG) contributes to pain hypersensitivity in the experimental autoimmune encephalomyelitis (EAE) mouse model of MS. Inflammatory cells and increased levels of ER stress markers are evident in post‐mortem DRGs from MS patients. Similarly, we observed ER stress in the DRG of mice with EAE and relieving ER st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 68 publications
(172 reference statements)
1
22
0
Order By: Relevance
“… 5 Induction of eIF2α phosphorylation is known to promote pain in a number of pathological conditions associated with sensory neuropathy. 7 , 36 , 102 To our surprise, we noted that type I interferons did not induce an eIF2α-mediated response in nociceptors. Rather, we observed induction of mitogen-activated protein kinase–interacting kinase (MNK1/2)-mediated eIF4E phosphorylation, 6 a different pathway that promotes the synthesis of proteins from a subset of mRNAs that are associated with promoting pain.…”
Section: Neurobiology Of Virus-induced Painmentioning
confidence: 76%
“… 5 Induction of eIF2α phosphorylation is known to promote pain in a number of pathological conditions associated with sensory neuropathy. 7 , 36 , 102 To our surprise, we noted that type I interferons did not induce an eIF2α-mediated response in nociceptors. Rather, we observed induction of mitogen-activated protein kinase–interacting kinase (MNK1/2)-mediated eIF4E phosphorylation, 6 a different pathway that promotes the synthesis of proteins from a subset of mRNAs that are associated with promoting pain.…”
Section: Neurobiology Of Virus-induced Painmentioning
confidence: 76%
“…The calcium-sensitive large conductance K + channels (BK) have recently been implicated in pain mechanisms during EAE ( 195 ). These channels are found in DRG neurons of mice with EAE and play a role in the endoplasmic reticulum (ER) stress-mediated pain response.…”
Section: The Role Of Ion Channels Pumps and Exchangers In Neuropathic Pain: Evaluating The Potential Contribution To Pain In Eaementioning
confidence: 99%
“…These channels are found in DRG neurons of mice with EAE and play a role in the endoplasmic reticulum (ER) stress-mediated pain response. It has been hypothesized that the prolonged neuroinflammation that occurs in the CNS during MS/EAE affects DRG neurons by conveying retrograde stress signals, which, in turn, induce ER stress ( 195 ). In fact, ER stress markers are elevated in post-mortem DRG of individuals with MS.…”
Section: The Role Of Ion Channels Pumps and Exchangers In Neuropathic Pain: Evaluating The Potential Contribution To Pain In Eaementioning
confidence: 99%
“…It has also been suggested that endoplasmic reticulum stress associated with nerve injury may contribute to pain by alteration of BK function (Yousuf et al, 2020).…”
Section: Distribution Of Intermediate Conductance K Ca Channels (K Camentioning
confidence: 99%